International Research Center for Centro di Architettura "Andrea Palladio": Vicenza, Italy - Dan Shepperd (Oz, 1982)
The medieval Center of Vicenza is dense, compacted by natural boundaries: the Retrone River to the south, the Bacchiglione River to the north, and the mountains to the west…